Primary intracranial alveolar soft part sarcoma in a 22 years old female: a rare case report with literature review - Muhammad Saad Babar; Qadri, Haseeb Mehmood; Ammara Tabassam; Muhammad Imran; Muhammad Hassan Raza (Journal of the Pakistan Medical Association, 2023)
Alveolar soft part sarcoma is a very rare malignant neoplasm of peripheral muscular, adipose or neural tissue. Its occurrence, as a primary intracranial tumour, is even rarer. To the best of our knowledge, only nine cases of primary intracranial alveolar soft part sarcoma exist in English scientific literature. We attempt to write a comprehensive review on this poorly understood intracranial malignancy, with no evident systemic lesions, such as in the case of our 22 years old patient. In addition to absent definitive proof of benefit of radiologic or chemotherapeutic management, we highlight the role of surgery as the primary treatment. Younger patients with this tumour may have a worse prognosis than elderly patients. Key words: alveolar soft part sarcoma, intracranial, headache, radiosurgery.